The voice of protest in English poetry : with special reference to poets of the first three decades of the twentieth century - Verschoor, Edith N E (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1973)
Poetry, like every other form of art, reflects the values of the artist himself as well as the values of the age in which he lives. "I would say that the poet may write about anything provided that the thing matters to him to start with, for then it will bring with it into the poem the intellectual or moral significance which it has for him in life". (Louis MacNeice). This thesis sets out to uncover some of the things which, in the long pageant of English poetry, have "mattered" to poets to such an extent that they have felt compelled to voice their protest against any violation of such things perceived by them in life around them. The basic study has been a search for the different kinds of values and codes of conduct, in social, political and moral spheres, which have been unacceptable to some of the major poets in English, and to examine particularly the manner and the tone of voice in which each one has expressed his disapproval. "Poetry was the mental rattle that awakened the attention of intellect in the infancy of civil society." (T.L.Peacock). English poets who have protested against whatever they regarded as worthy of protest have continued up to the maturity of civil society to be rattles (some soft and mellow, others loud and harsh), to awaken both the intellect and the conscience of their readers.
Keywords: Protest poetry, English -- History and criticism; English poetry -- History and criticism; English poetry -- 20th century -- History and criticism